2010
DOI: 10.2136/sssaj2009.0123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Reduction on Phosphorus Sorption of an Organic‐Rich Silt Loam

Abstract: Phosphorus flux from agricultural landscapes to surface waters may cause eutrophication. In the northeastern United States, P transport largely depends on P sorption of soils in variable source areas or in land treatment systems. Soil redox fluctuation commonly occurs in these areas. Nevertheless, the effect of soil redox on P sorption has been variable in the literature. This study investigated P sorption of an organic‐rich northeastern glaciated silt loam (Langford) under air‐dried, field‐wet, and reduced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
0
24
0
3
Order By: Relevance
“…During the fall period the soil temperature is still relatively warm so the labile pool of P, especially the organic fraction of ligand exchange and complexation, is still quite active and decomposing. Spreading manure wastewater at this time has the effect of decreasing the zero-sorption P equilibrium concentration and reducing the amount of P that can be stored in the labile pool [60]. In addition, the mineralization and subsequent accumulation of P in the summer may add to the leaching of P in the fall.…”
Section: Relationship Between Groundwater Srp Concentrations Temperamentioning
confidence: 99%
“…During the fall period the soil temperature is still relatively warm so the labile pool of P, especially the organic fraction of ligand exchange and complexation, is still quite active and decomposing. Spreading manure wastewater at this time has the effect of decreasing the zero-sorption P equilibrium concentration and reducing the amount of P that can be stored in the labile pool [60]. In addition, the mineralization and subsequent accumulation of P in the summer may add to the leaching of P in the fall.…”
Section: Relationship Between Groundwater Srp Concentrations Temperamentioning
confidence: 99%
“…Reactive iron in the solid phase has a profound influence on the geochemistry of marine sediments (Canfield 1989;Giblin and Howarth 1984), as the reactive iron was involved in the formation of pyrite (Berner 1970;Jorgensenb 1978;Oenema 1990), the release of phosphate (Mortimer 1941), and the precipitation of trace metals (Jenne 1977). Reactive iron can also enhance the sorption of dissolved inorganic phosphorus in reductive soil (Zhang et al 2010). Both the reactive iron and crystalline iron existed as divalent Fe(II) and trivalent Fe(III).…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove forest, being a salt marsh environment, the biogeochemical transformation of Fe in it is very important as Fe cycling is closely associated with carbon (C) and sulfur (S) cycles via microbial mediation in salt marshes (Kostka and Luther Responsible editor: Céline Guéguen 1995); also, it affects the bioavailability of nutrient elements (e.g., P) and toxicity of metallic pollutants (e.g., Cd) in sediments (Prasad and Ramanathan 2010;Marchand et al 2006;Neubauer et al 2007). Zhang et al (2010) reported that the switching of Fe oxidation-reduction is affected by chemical factors including Eh, pH, O 2 , organic matter, and inorganic ligands. Among the various inorganic ligands that interact with Fe, P has drawn special attention because P is also of great biological importance.…”
Section: Introductionmentioning
confidence: 99%
“…Soil drainage has also been shown to influence nitrogen cycling in many types of land uses (Addy et al, 1999;Mosier et al, 2002;van Es et al, 2002;Young and Briggs, 2007). Furthermore, fluctuating water tables can influence a soil's redox status, which in turn may have a significant effect on phosphorus retention in soils (Sims and Pierzynski, 2005;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%